Diagnosis and management in Pitt‐Hopkins syndrome: First international consensus statement. Issue 4 (18th February 2019) - Zollino, Marcella; Zweier, Christiane; Van Balkom, Ingrid D.; Sweetser, David A.; Alaimo, Joseph; Bijlsma, Emilia K.; Cody, Jannine; Elsea, Sarah H.; Giurgea, Irina; Macchiaiolo, Marina; Smigiel, Robert; Thibert, Ronald L.; et al.
Abstract : Pitt‐Hopkins syndrome (PTHS) is a neurodevelopmental disorder characterized by intellectual disability, specific facial features, and marked autonomic nervous system dysfunction, especially with disturbances of regulating respiration and intestinal mobility. It is caused by variants in the transcription factor TCF4 . Heterogeneity in the clinical and molecular diagnostic criteria and care practices has prompted a group of international experts to establish guidelines for diagnostics and care. For issues, for which there was limited information available in international literature, we collaborated with national support groups and the participants of a syndrome specific international conference to obtain further information. Here, we discuss the resultant consensus, including the clinical definition of PTHS and a molecular diagnostic pathway. Recommendations for managing particular health problems such as dysregulated respiration are provided. We emphasize the need for integration of care for physical and behavioral issues. The recommendations as presented here will need to be evaluated for improvements to allow for continued optimization of diagnostics and care. Abstract :